STABILITY OF LOCAL RAW MATERIALS FOR MUD CRAB FEED DEVELOPMENT - Johannes Hutabarat (JOURNAL OF COASTAL DEVELOPMENT, 1997)
The aims of study were to identify the potency and nutritional values of local raw materials available in Central java, and to develop the mud crab feed using selected raw materials for its deffatening culture. The potency level of local raw materials was determined by using secondary data available in relevant technical institution e.g. Agriculture Department, Fisheries Bureau and followed by direct site survey in the production centre of agriculture and fisheries by catch in Central Java, i.e Pekalongan, Kendal, Semarang, Jepara, Pati and Rembang. Data obtained were analyzed descriptively to determine the resource of the potentials of local raw materials and followed by determining their nutritional values, profile and availability of assential amino acids (EAA) and essential fatty acids (EFA), using standard method available. The results indicated that the local raw materials for protein sources are found in abundance in Central Java throughout the year with relatively cheap price i.e: trash fish, mysid, squid, blood meals, worm-meals and shrimp head-meals (animal protein) and saga, soybeans (plant protein). The protein level of selected raw materials were high (41.15% – 80.35%) and the highest level was found in blood meal and followed by squid, trash fish and shrimp head meals. The selected raw materials, generally contains 10 essential amino acids (Arginine, lysine, histidine, phenylalanine, leucine, isoleucine, methionine, valine, threonine, and trypthophane) and a long chain of EFA (n-3 HUFA) and (n-6 HUFA) which are required by mud crab for their growth. The selected local raw materials are therefore nutritionally suitable for mud crab feed development in Central Java.